Assessing Income Tax Perturbations - Vidar Christiansen; Zhiyang Jia; Mr Thor Olav Thoresen (Center for Economic Studies and ifo Institute (CESifo), 2018)
Taking a piecemeal tax reform approach to tax analysis in the spirit of Feldstein (1976), we establish a framework for assessing perturbations of the income tax schedule. It decomposes a reform into a change in tax level and a structural reform part. Focussing on the latter, the analysis singles out four effects: A social efficiency effect measured as the change in tax revenue due to behavioural changes, distributional impact due to mechanical effects, total distributional effects, and overall welfare effects conditional on inequality aversion. When applying our approach to changes in the piecewise linear income tax in Norway during 2016-2018, we identify the cut-off value for the inequality aversion for which the reform is just welfare preserving. For lower inequality aversion the decision makers have accepted a reform which enhances social efficiency at the expense of redistribution in favour of the better-off households.
Keywords: H21; 330; income tax; tax reform; tax perturbation